Development of an antisense strategy to down-regulate gene expression in chronic myelogenous leukaemia - O'Connor, Lisa M. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2005)
Since the discovery of mRNA down-regulation by sequences of complementary nucleic acids in 1977, there has been a drive to apply the antisense phenomenon to therapeutic settings. In theory the potential of antisense therapeutics is extensive, however practically, antisense-based therapeutics are not yet widely applied due to limitations and secondary effects of antisense chemistries. This thesis examines the impact of existing and novel antisense backbones on the expression of the Chronic Myelogenous Leukaemia specific protein, BCR-ABL. Novel chemistries examined include the morpholino which prevents the translation of target mRNA transcripts by steric hindrance, and the RNAi approach which utilises anti-pathogenic pathways to mediate mRNA destruction.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin